INTERPERSONAL COMMUNICATION STRATEGY OF TRAINERS AND PLAYERS IN IMPROVING THE ACHIEVEMENT OF THE FUTSAL TEAM OF UPI BANDUNG (Qualitative Study of Putri UPI Bandung Futsal Team) - Arief Kurniawan (IKIP Siliwangi Bandung, 2018)
Abstract: Interpersonal Communication Strategy for Trainers and Players in Improving the Achievement of UPI Bandung Futsal Team. Interpersonal communication is communication that has a large effect in terms of changing the attitudes and thoughts of others, especially individuals. This is because, usually the parties involved in the communication meet directly, do not use the media in delivering the message so that there is no distance that separates the communicator from the communicant. The diversity of the UPI Bandung Futsal Club players led to the need for an appropriate communication in a training situation and at the time of evaluation after the training of the players. Interpersonal communication is considered necessary to be used and controlled by a trainer in communicating to players during training in the field as well as interactions outside the field. UPI Bandung Futsal Club has three training programs, including strategy training, physical training, and agility training. Good communication will facilitate the process of sending the intended message from the coach, so that if what is instructed from the three training programs by the trainer then performed well by the player. The author chooses the effectiveness of Interpersonal communication between the trainer and the UPI Bandung Futsal Club player, because researchers are interested in the background of the different tribes of players and the players who are women. In addition, an increase in achievement adds to the interest of researchers to find out more about interpersonal communication at the UPI Bandung Futsal Club in improving achievementThis study aims to describe and analyze How Interpersonal Communication Strategies for Trainers and Players Improve UPI Bandung Futsal Team Achievement (Qualitative Study of Teams Putri UPI futsal Bandung).